Differential Effects of 10 and 20 Hz Brain Stimulation in Chronic Stroke: A tACS-fMRI Study - Kai Yuan; Cheng Chen; Wu-Tao Lou; Ahsan Khan; Eden Chun-Hang Ti; Cathy Choi-Yin Lau; Xin Wang; Winnie Chiu-Wing Chu; Raymond Kai-Yu Tong (IEEE, 2022)
Transcranial alternating current stimulation (tACS) is an emerging non-invasive neuromodulation technique, which could be potentially applied to enhance stroke rehabilitation. In this study, we aimed to characterize the frequency-specific effects of tACS in chronic stroke. Therefore, concurrent tACS and functional magnetic resonance imaging (fMRI) were conducted in 13 chronic stroke individuals. Resting-state and task-based fMRI were collected for each subject under different frequencies (10 Hz, 20 Hz, Sham). Task-based fMRI showed that increased activation was found in the ipsilesional precentral area during paretic hand movements after 10 Hz tACS, while increased activation was found in the contralesional precentral area during non-paretic hand movements after both 10 and 20 Hz tACS. Resting-state seed-based functional connectivity (FC) analysis showed that 10 Hz tACS mainly modulated FC within motor-related regions, while 20 Hz tACS also modulated regions beyond the motor-related areas. Graph theory analysis further demonstrated the functional interaction modulated by tACS in the whole-brain level. Taken together, our results showed that tACS might exhibit frequency-specific modulation in chronic stroke. 20 Hz tACS facilitates the functional interaction between the sensorimotor regions and brain regions involved in executive control, while 10 Hz and sham tACS has limited effect on motor-related brain activity. Our results reveal the neural response process under external current stimulation, providing new insight into the neuromodulation mechanism of tACS in a lesioned brain.